A high‐quality reprocessed ground‐based GPS dataset for atmospheric process studies, radiosonde and model evaluation, and reanalysis of HyMeX Special Observing Period. (17th February 2016) - Bock, O.; Bosser, P.; Pacione, R.; Nuret, M.; Fourrié, N.; Parracho, A.
Abstract : In the framework of the Hydrological cycle in the Mediterranean Experiment (HyMeX) project, measurements from more than 1000 ground‐based Global Positioning System (GPS) receivers located in the northwestern Mediterranean area are reprocessed using a single piece of GPS software for the period from 1 September 2012 to 31 March 2013. A special screening procedure is developed for the removal of outliers in the GPS Zenith Total Delay (ZTD) data. ZTD data are converted to integrated water vapour (IWV) using surface pressure information from an AROME‐WMED operational analysis. The reprocessed ZTD and IWV data are used to assess the accuracy of the near‐real time E‐GVAP ZTD data assimilated in operational numerical weather prediction systems and to validate the IWV data from the AROME‐WMED operational analysis and AROME‐WMED reanalysis 1, and from radiosonde observations. The mean differences between E‐GVAP and reprocessed ZTD data are not negligible and lie in the range from −3 to +3 mm. The standard deviations of differences are between 4 and 8 mm. The comparisons of IWV from AROME‐WMED analyses and the reprocessed GPS data show high quality of the analyses where operational GPS data are assimilated and lower quality where no GPS data are assimilated. Small but significant biases are found in the radiosonde data during daytime (−0.5 to +1.4 kg m −2 ), but their origin is not determined so far. Thanks to the high spatial density of the reprocessed GPS stations, both the large‐scale and small‐scale variations in IWV can be documented. The case of HyMeX Intensive Observing Period 8 is presented as an example of a heavy precipitation event. This work suggests that improved quality of the humidity fields can be expected of the future AROME‐WMED reanalysis 2 as a result of the assimilation of the reprocessed GPS data.